The ground for the illiberal turn in the Philippines. Issue 4 (19th May 2022) - Garrido, Marco
ABSTRACT: We know a lot about the new wave of autocrats and how they operate but much less about why so many people, particularly in the developing world, are cheering them on. Case-in-point: How do we make sense of widespread popular support for Philippine president Rodrigo Duterte's strongman rule? Scholars generally cite frustration with a democracy widely regarded as elite-dominated and endemically corrupt, but this account is underspecified. Filipinos have been frustrated with liberal democracy for a long time and Duterte is not the first law-and-order candidate to seek the presidency. I will argue that we need to situate Duterte's election and enduring appeal in the conversation about democracy as it has unfolded on the ground. Specifically, (1) repeated failures to reform democracy have resulted in (2) conditional support for democracy and increasing openness to certain authoritarian forms of government. (3) These attitudes manifest on the ground as calls for "disciplining" democracy. (4) Rodrigo Duterte is seen as a "strong leader" and the answer to such calls, hence his enormous popularity. I will provide evidence for each of these claims and make the case for grounding the illiberal turn in people's experience of democracy.